Arthrodesis of the Second and Third Tarsometatarsal Joints: Comparison of Radiological and Clinical Results Using Combined or Individual Plating Techniques - Tom Ankers; Anjani Singh; Christopher R Walker; Lyndon W Mason; Siva Sirikonda (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: Arthrodesis is an effective treatment of midfoot arthritis in reducing pain and improving function. However, there is a known risk of nonunion. Our aim was to compare the outcomes of individual plating vs combined plating for the fusion of both the second and third tarsometatarsal joints (TMTJs). Our primary outcome was bone healing, and secondary outcomes include patient-reported outcome measures. Methods: All cases underwent primary arthrodesis of the second and third TMTJs. Arthrodesis was performed using either a single “H-shaped” plate (combined plating group) or using two separate plates (individual plating group). The outcome measures were bony union and the Manchester Oxford Foot Questionnaire score (MOX-FQ). Results: A total of 45 procedures were undertaken with a mean follow-up of 527 days. The combined plating group had 28 cases, and the individual plating group had 17 cases. There were 10 cases (35.71%) of nonunion in the combined plating group and two cases (11.76%) in the individual plating group. Multivariate regression analysis showed a significant relationship of union with the use of the individual plating group [p = 0.047, odds ratio (OR) 5.822]. Patients who had also undergone the first TMTJ fusion had an increased chance of union (p = 0.043, OR 9.896). No other factors showed significance. MOX-FQ scores were superior in the individual group at 6 months postsurgery, although this statistical significance was lost when the nonunions were excluded. Conclusion: This study is the first to report a difference in the union between combined plating and individual plating techniques in arthrodesis of the second and third TMTJs. We believe that individual plates permit a more anatomical reduction and greater compression at the site of arthrodesis as compared to a dual plate technique, achieving better union results and an early better functional outcome.